Freezing cold injuries among soldiers in the Norwegian Armed Forces - A cross sectional study - Steinberg, Tuva; Kristoffersen, Agnete; Bjerkan, Geir; Norheim, Arne Johan (International journal of circumpolar health, 2023)
Introduction: Freezing cold injuries (FCI) are a common risk in extreme cold weather warfare operations. The Norwegian Armed Forces (NAF) have the expertise and capabilities in education and training for warfighting capabilities in the Arctic. Nevertheless, a substantial number of Norwegian soldiers sustain freezing cold injuries annually. The aim of this study was to describe the FCI in the NAF, the associated risk factors and clinical associations. Methodology: The subjects for the study were soldiers registered with FCI in the Norwegian Armed Forces Health Registry (NAFHR) between January 1st 2004-July1st 2021. The soldiers answered a questionnaire regarding background, activities at the time of injury, description of the FCI, risk factors, medical treatment and any sequelae from their FCI. Results: FCI in the NAF were most frequently reported among young conscripts (mean20.5 years). Hands and feet are most often injured (90.9%). Only a minority (10.4%) received medical treatment. The majority (72.2%) report sequelae. Extreme weather conditions was the most important risk factor (62.5%). Conclusions: Most soldiers had the knowledge to avoid FCI, but they were injured anyway. It is concerning that only one in 10 injured soldiers received medical treatment after diagnosed with FCI, increasing the risk of FCI sequelae.